2017
DOI: 10.1007/s10457-017-0159-5
|View full text |Cite
|
Sign up to set email alerts
|

Shade trees decrease pest abundances on brassica crops in Kenya

Abstract: Agroforestry practices may mitigate the current loss of biodiversity and ecosystem services due to deforestation and agricultural intensification. To examine the effects of agroforestry on the ecosystem service of pest regulation, we assessed pest abundances and biological control potential in shaded and open kale (Brassica oleracea L. acephala) fields in Western Kenya. Specifically, we compared the abundance of pest aphids and caterpillars, ground-dwelling ants, spiders and predatory beetles, and examined aph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In the desert, rocks and vegetation play additional ecological roles beyond that of thermal shelter. In various ecological systems, rocks increase prey abundance and diversity (Borkhataria et al, 2012;Guenat et al, 2017;Johnson, 2000), reduce competition, foodsearching movement, and increase foraging efficiency (Attum & Eason, 2006;Belliure et al, 1996;Kearney et al, 2021), reduce escape distances from predators (Amo et al, 2007;Huey, 1991;Monasterio et al, 2010;Newbold & MacMahon, 2014;Pietrek et al, 2009), and reduce water loss (Rozen-Rechels et al, 2019). In desert habitats where rocks are less abundant (like sandy deserts), bushes, trees, and burrows may provide most of the shade (Cain et al, 2008) and protection from predation (Pietrek et al, 2009) and competition (Zeng et al, 2016); such habitats may be at risk due to novel warmer and drier climates (Kim et al, 2018;Levy, Buckley, et al, 2016b), invasive species (Garcia & Clusella-Trullas, 2019), and habitat loss (Estavillo et al, 2013).…”
Section: Ecological Importance Of Rocks and Vegetationmentioning
confidence: 99%
“…In the desert, rocks and vegetation play additional ecological roles beyond that of thermal shelter. In various ecological systems, rocks increase prey abundance and diversity (Borkhataria et al, 2012;Guenat et al, 2017;Johnson, 2000), reduce competition, foodsearching movement, and increase foraging efficiency (Attum & Eason, 2006;Belliure et al, 1996;Kearney et al, 2021), reduce escape distances from predators (Amo et al, 2007;Huey, 1991;Monasterio et al, 2010;Newbold & MacMahon, 2014;Pietrek et al, 2009), and reduce water loss (Rozen-Rechels et al, 2019). In desert habitats where rocks are less abundant (like sandy deserts), bushes, trees, and burrows may provide most of the shade (Cain et al, 2008) and protection from predation (Pietrek et al, 2009) and competition (Zeng et al, 2016); such habitats may be at risk due to novel warmer and drier climates (Kim et al, 2018;Levy, Buckley, et al, 2016b), invasive species (Garcia & Clusella-Trullas, 2019), and habitat loss (Estavillo et al, 2013).…”
Section: Ecological Importance Of Rocks and Vegetationmentioning
confidence: 99%
“…This type of interaction is likely to influence the presence of diseases. The action of shade trees on the understory microclimate decreases with decreasing distance between trees and pathogen transmission decreases as the distance between host individuals increases [51,52,[57][58][59].…”
Section: Complex Cocoa-based Agroforest Systems and Structural Characteristicsmentioning
confidence: 99%
“…Shade trees play various roles in tropical agroforests. They can improve adverse weather conditions by modulating temperature variations [51,52,57,59]. Shading has been recognized as one of the factors that can influence PLFSD dissemination [54,67,68].…”
Section: Effect Of Shade Intensity Management On Cdp and Plfsdmentioning
confidence: 99%
“…AFS has often been touted as a land-use system that can contribute to natural pest control, the increase in structural diversity can augment the functional biodiversity of the site, thus benefiting the natural antagonists of crop pests [161,162]. Recent research and meta-analyses have shown that trees in agricultural lands were likely to be providing refuge to insectivorous vertebrates and ground dwelling natural predators [162,163] although this is most likely pest species-dependent while also being dependent on crop and tree species combinations [161]. Meanwhile, it is also reported that the presence of trees does not necessarily increase the resilience of AFS against antagonists alone, but in combination with microclimatic conditions that influence pest performance, crop growth and soil conditions [163].…”
Section: Contribution To Natural Pest Controlmentioning
confidence: 99%
“…Recent research and meta-analyses have shown that trees in agricultural lands were likely to be providing refuge to insectivorous vertebrates and ground dwelling natural predators [162,163] although this is most likely pest species-dependent while also being dependent on crop and tree species combinations [161]. Meanwhile, it is also reported that the presence of trees does not necessarily increase the resilience of AFS against antagonists alone, but in combination with microclimatic conditions that influence pest performance, crop growth and soil conditions [163]. Further research and empirical study is needed to increase the understanding of the relationships between tree cover, food webs and natural pest suppression [161,162] with the development and testing of crop-pest modelling tools in multiple AFS systems of varying complexity.…”
Section: Contribution To Natural Pest Controlmentioning
confidence: 99%